Book review : Cuba, Africa, and Apartheid's end : Africa's children return ! [compte-rendu de lecture] - (:unkn) unknown (My University, 2023)
Isaac Saney offers an authoritative account of Cuba's role in liberating Namibia and South Africa that is centred on the battle of Cuito Cuanavale (1987-1988). With skilful attention to detail and a meticulous use of sources, the book exposes the full breath of Cuba's internationalism and updates the historical and symbolic ties between the Caribbean island and the African continent.
Keywords: African Research